The origins of neutron-capture elements in globular cluster M22 - Ashraf, Muhammad Zeshan; Cui, Wenyuan; Li, Hongjie (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThe chemical abundances of metal poor (MP) stars in globular clusters provide valuable information for constraining their evolutionary scenarios.MethodsUsing both main r-process and weak r-process patterns, we fit the abundances of s-poor stars in the globular cluster M22.Results and discussionThe coefficients of the main and weak r-process components are nearly constant for the sample stars, including s-rich stars. By considering the contribution of the s-process from low-mass AGB stars, the abundances of s-rich stars in M22 can also be fitted effectively. Furthermore, the increasing trend in the s-process component coefficients (Cs) with increasing [Fe/H] suggests a gradual increase in the contribution from low-mass AGB stars.